Methods and Approaches for Automatic Processing and Storage of High-Potential Electrocardiogram Registered by Hardware and Software Complex on Nanosensors; MATEC Web of Conferences; Vol. 155 : Information and Measuring Equipment and Technologies (IME&T 2017) - Rybalka S. A. Sergey Anatolyevich; Yuzhakov M. M. Mikhail Mikhaylovich; Ivanov M. L. Maxim Leonidovich; Nguyen Dang Quang; Kodermjatov R. Radik; Guo Wenjia; Maksimov I. Ivan; Zimin I. Ilya (2018, 2018)
Title screen